Assessment of the optical and electrical properties of light-emitting diodes containing carbon-based nanostructures and plasmonic nanoparticles: a review - Nagpal, Keshav; Rauwel, Erwan; Ducroquet, Frédérique; Rauwel, Protima (Beilstein Journal of Nanotechnology, 2021)
Light-emitting diodes (LED) are widely employed in display applications and lighting systems. Further research on LED that incorporates carbon nanostructures and metal nanoparticles exhibiting surface plasmon resonance has demonstrated a significant improvement in device performance. These devices offer lower turn-on voltages, higher external quantum efficiencies, and luminance. De facto, plasmonic nanoparticles, such as Au and Ag have boosted the luminance of red, green, and blue emissions. When combined with carbon nanostructures they additionally offer new possibilities towards lightweight and flexible devices with better thermal management. This review surveys the diverse possibilities to combine various inorganic, organic, and carbon nanostructures along with plasmonic nanoparticles. Such combinations would allow an enhancement in the overall properties of LED.
Keywords: carbon nanotubes (CNT); graphene; light-emitting diodes (LED); plasmonic nanoparticles; quantum dots

(untitled) - Salata, O. V. (J. Nanobiotechnol., 2004)

(untitled) - Kolahalam, L. A.; Kasi Viswanath, I. V.; Diwakar, B. S.; Govindh, B.; Reddy, V.; Murthy, Y. L. N. (Mater. Today, 2019)

(untitled) - Gayral, B. (C. R. Phys., 2017)

(untitled) - Carr, W. N.; Pittman, G. E. (Appl. Phys. Lett., 1963)

(untitled) - Steranka, F. M. (Semicond. Semimetals, 1997)

(untitled) - Kish, F. A.; Fletcher, R. M. (Semicond. Semimetals, 1997)

(untitled) - Nakamura, S. (Proc. SPIE, 1997)

(untitled) - Lin, Q.; Song, B.; Wang, H.; Zhang, F.; Chen, F.; Wang, L.; Li, L. S.; Guo, F.; Shen, H. (J. Mater. Chem. C, 2016)

(untitled) - Sahbudin, U. K.; Wahid, M. H. A.; Poopalan, P.; Hambali, N. A. M. A.; Shahimin, M. M.; Ariffin, S. N.; Saidi, N. N. A.; Ramli, M. M. (MATEC Web Conf., 2016)

(untitled) - Jang, E.-P.; Han, C.-Y.; Lim, S.-W.; Jo, J.-H.; Jo, D.-Y.; Lee, S.-H.; Yoon, S.-Y.; Yang, H. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Rahman, F. (Opt. Eng. (Bellingham, WA, U. S.), 2019)

(untitled) - Neves, M. C.; Martins, M. A.; Soares-Santos, P. C. R.; Rauwel, P.; Ferreira, R. A. S.; Monteiro, T.; Carlos, L. D.; Trindade, T. (Nanotechnology, 2008)

(untitled) - Tsukazaki, A.; Kubota, M.; Ohtomo, A.; Onuma, T.; Ohtani, K.; Ohno, H.; Chichibu, S. F.; Kawasaki, M. (Jpn. J. Appl. Phys., Part 2, 2005)

Handbook of Organic Materials for Electronic and Photonic Devices (Second Edition) - Will, P.-A.; Reineke, S. (Organic light-emitting diodes, 2019)

(untitled) - He, Y.; Cheng, N.; Xu, X.; Fu, J.; Wang, J.-a. (Org. Electron., 2019)

(untitled) - Ahn, J. H.; Wang, C.; Pearson, C.; Bryce, M. R.; Petty, M. C. (Appl. Phys. Lett., 2004)

(untitled) - Mueller, T.; Kinoshita, M.; Steiner, M.; Perebeinos, V.; Bol, A. A.; Farmer, D. B.; Avouris, P. (Nat. Nanotechnol., 2010)

(untitled) - Wang, G.-F.; Tao, X.-M.; Wang, R.-X. (Compos. Sci. Technol., 2008)

(untitled) - Fournet, P.; Coleman, J. N.; Lahr, B.; Drury, A.; Blau, W. J.; O’Brien, D. F.; Hörhold, H.-H. (J. Appl. Phys., 2001)

(untitled) - Liu, G.; Johnson, S.; Kerr, J. B. (MRS Online Proc. Libr., 2003)

(untitled) - Aguirre, C. M.; Auvray, S.; Pigeon, S.; Izquierdo, R.; Desjardins, P.; Martel, R. (Appl. Phys. Lett., 2006)

(untitled) - Jeong, S.-H.; Choi, H.; Kim, J. Y.; Lee, T.-W. (Part. Part. Syst. Charact., 2015)

(untitled) - Liu, F.; Nunzi, J.-M. (Proc. SPIE, 2012)

(untitled) - Lee, I.-H.; Jang, L.-W.; Polyakov, A. Y. (Nano Energy, 2015)

(untitled) - Khadir, S.; Chakaroun, M.; Belkhir, A.; Fischer, A.; Lamrous, O.; Boudrioua, A. (Opt. Express, 2015)

(untitled) - Diallo, A. T.; Chakaroun, M.; Khadir, S.; Hamdad, S.; Esparza-Villa, J. U.; Maître, A.; Boudrioua, A. (J. Nanophotonics, 2019)

(untitled) - Hong, S.-H.; Cho, C.-Y.; Lee, S.-J.; Yim, S.-Y.; Lim, W.; Kim, S.-T.; Park, S.-J. (Opt. Express, 2013)

(untitled) - Chen, H.-S.; Yang, P.; Khan, Z. H.; Wu, J. M.; Li, G.; Kamali, A. R. (J. Nanomater., 2015)

(untitled) - Bhaumik, S.; Ghosh, B.; Pal, A. J. (Appl. Phys. Lett., 2011)

(untitled) - Ameera, N.; Shuhaimi, A.; Surani, N.; Rusop, M.; Hakim, M.; Mamat, M. H.; Mansor, M.; Sobri, M.; Ganesh, V.; Yusuf, Y. (Ceram. Int., 2015)

(untitled) - Ling, B.; Sun, X. W.; Zhao, J. L.; Ke, C.; Tan, S. T.; Chen, R.; Sun, H. D.; Dong, Z. L. (J. Phys. Chem. C, 2010)

(untitled) - Keller, J.; Stolt, L.; Edoff, M.; Törndahl, T. (Phys. Status Solidi A, 2016)

(untitled) - Li, S.; Shi, Z.; Tang, Z.; Li, X. (Vacuum, 2017)

(untitled) - Liu, H.; Avrutin, V.; Izyumskaya, N.; Özgür, Ü.; Morkoç, H. (Superlattices Microstruct., 2010)

(untitled) - Kim, H.; Gilmore, C. M.; Piqué, A.; Horwitz, J. S.; Mattoussi, H.; Murata, H.; Kafafi, Z. H.; Chrisey, D. B. (J. Appl. Phys., 1999)

(untitled) - Bonaccorso, F.; Sun, Z.; Hasan, T.; Ferrari, A. C. (Nat. Photonics, 2010)

(untitled) - Han, N.; Viet Cuong, T.; Han, M.; Deul Ryu, B.; Chandramohan, S.; Bae Park, J.; Hye Kang, J.; Park, Y.-J.; Bok Ko, K.; Yun Kim, H.; Kyu Kim, H.; Hyoung Ryu, J.; et al. (Nat. Commun., 2013)

(untitled) - Fu, Y.; Hansson, J.; Liu, Y.; Chen, S.; Zehri, A.; Samani, M. K.; Wang, N.; Ni, Y.; Zhang, Y.; Zhang, Z.-B.; Wang, Q.; Li, M.; et al. (2D Mater., 2019)

(untitled) - Kim, B.-J.; Lee, C.; Jung, Y.; Hyeon Baik, K.; Mastro, M. A.; Hite, J. K.; Eddy, C. R., Jr; Kim, J. (Appl. Phys. Lett., 2011)

(untitled) - Guo, X.; Feng, Y.; Liu, Q.; Hu, A.; He, X.; Hu, Z. (J. Appl. Phys., 2018)

(untitled) - Bae, S.; Kim, H.; Lee, Y.; Xu, X.; Park, J.-S.; Zheng, Y.; Balakrishnan, J.; Lei, T.; Ri Kim, H.; Song, Y. I.; Kim, Y.-J.; Kim, K. S.; et al. (Nat. Nanotechnol., 2010)

(untitled) - Shim, J.-P.; Hoon Seo, T.; Min, J.-H.; Mo Kang, C.; Suh, E.-K.; Lee, D.-S. (Appl. Phys. Lett., 2013)

(untitled) - Hoon Seo, T.; Kyoung Kim, B.; Shin, G.; Lee, C.; Jong Kim, M.; Kim, H.; Suh, E.-K. (Appl. Phys. Lett., 2013)

(untitled) - Tanaka, T.; Totoki, Y.; Fujiki, A.; Zettsu, N.; Miyake, Y.; Akai-Kasaya, M.; Saito, A.; Ogawa, T.; Kuwahara, Y. (Appl. Phys. Express, 2011)

(untitled) - Jin, Y.; Li, Q.; Li, G.; Chen, M.; Liu, J.; Zou, Y.; Jiang, K.; Fan, S. (Nanoscale Res. Lett., 2014)

(untitled) - Guo, X.; Guo, C. W.; Jin, Y. H.; Chen, Y.; Li, Q. Q.; Fan, S. S. (Nanoscale Res. Lett., 2014)

(untitled) - Kim, J.-Y.; Kim, M.; Kim, H.; Joo, J.; Choi, J.-H. (Opt. Mater. (Amsterdam, Neth.), 2003)

(untitled) - Shin, J. B.; Baek, S.-W.; Lee, S. M.; Kim, M.; Lee, J.-Y.; Choi, K. C. (IEEE Photonics Technol. Lett., 2016)

(untitled) - Choi, J.; Kim, S.; Park, C. H.; Kwack, J. H.; Park, C. H.; Hwang, H.; Im, H.-S.; Park, Y. W.; Ju, B.-K. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Jesuraj, P. J.; Jeganathan, K.; Navaneethan, M.; Hayakawa, Y. (Synth. Met., 2016)

(untitled) - Feng, J.; Sun, D.; Mei, S.; Shi, W.; Mei, F.; Zhou, Y.; Xu, J.; Jiang, Y.; Wu, L. (Front. Mater., 2018)

(untitled) - Zhou, L.; Xiang, H.-Y.; Zhu, Y.-F.; Ou, Q.-D.; Wang, Q.-K.; Du, J.; Hu, R.; Huang, X.-B.; Tang, J.-X. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Wang, S.; Zeng, Q.; Yang, L.; Zhang, Z.; Wang, Z.; Pei, T.; Ding, L.; Liang, X.; Gao, M.; Li, Y.; Peng, L.-M. (Nano Lett., 2011)

(untitled) - Prasad, N.; Singh, I.; Kumari, A.; Madhwal, D.; Madan, S.; Dixit, S. K.; Bhatnagar, P. K.; Mathur, P. C. (J. Lumin., 2015)

(untitled) - Nam Nguyen, P. H.; Nguyen, N. D. (Adv. Nat. Sci.: Nanosci. Nanotechnol., 2013)

(untitled) - Cao, S.; Zheng, J.; Zhao, J.; Yang, Z.; Li, C.; Guan, X.; Yang, W.; Shang, M.; Wu, T. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Shi, Z.; Li, Y.; Li, S.; Li, X.; Wu, D.; Xu, T.; Tian, Y.; Chen, Y.; Zhang, Y.; Zhang, B.; Shan, C.; Du, G. (Adv. Funct. Mater., 2018)

(untitled) - Lee, C.-Y.; Chen, Y.-M.; Deng, Y.-Z.; Kuo, Y.-P.; Chen, P.-Y.; Tsai, L.; Lin, M.-Y. (Nanomaterials, 2020)

(untitled) - Coe, S.; Woo, W.-K.; Bawendi, M.; Bulović, V. (Nature, 2002)

(untitled) - Huang, C.-Y.; Lai, J.-H. (Org. Electron., 2016)

(untitled) - Jayabharathi, J.; Prabhakaran, A.; Thanikachalam, V.; Sundharesan, M. (J. Photochem. Photobiol., A, 2016)

(untitled) - Wang, G.-F.; Tao, X.-M.; Chen, W.; Wang, R.-X.; Yang, A. (J. Lumin., 2007)

(untitled) - Yang, J.; Lee, J.; Lee, J.; Park, T.; Ahn, S. J.; Yi, W. (Diamond Relat. Mater., 2017)

(untitled) - Shi, S.; Sadhu, V.; Moubah, R.; Schmerber, G.; Bao, Q.; Silva, S. R. P. (J. Mater. Chem. C, 2013)

(untitled) - Lin, C.-H.; Chen, K.-T.; Ho, J.-R.; Cheng, J.-W. J.; Tsiang, R. C.-C. (J. Nanotechnol., 2012)

(untitled) - Park, M.; Nguyen, T. P.; Choi, K. S.; Park, J.; Ozturk, A.; Kim, S. Y. (Electron. Mater. Lett., 2017)

(untitled) - Jung, M.; Mo Yoon, D.; Kim, M.; Kim, C.; Lee, T.; Hun Kim, J.; Lee, S.; Lim, S.-H.; Woo, D. (Appl. Phys. Lett., 2014)

(untitled) - Jenekhe, S. A.; Zhang, X.; Chen, X. L.; Choong, V.-E.; Gao, Y.; Hsieh, B. R. (Chem. Mater., 1997)

(untitled) - Tardy, J.; Khalifa, M. B.; Vaufrey, D. (Mater. Sci. Eng., C, 2006)

(untitled) - Park, M.; Song, J.; An, M.; Lim, J.; Lee, C.; Roh, J.; Lee, D. (RSC Adv., 2020)

(untitled) - Strukelj, M.; Miller, T. M.; Papadimitrakopoulos, F.; Son, S. (J. Am. Chem. Soc., 1995)

(untitled) - Choudhary, R. B.; Mandal, G. (J. Mater. Sci.: Mater. Electron., 2020)

(untitled) - Alam, M. B.; Yadav, K.; Shukla, D.; Srivastava, R.; Lahiri, J.; Parmar, A. S. (ChemistrySelect, 2019)

(untitled) - Park, J. S.; Lee, J. M.; Hwang, S. K.; Lee, S. H.; Lee, H.-J.; Lee, B. R.; Park, H. I.; Kim, J.-S.; Yoo, S.; Song, M. H.; Kim, S. O. (J. Mater. Chem., 2012)

(untitled) - He, X.; Wang, W.; Li, S.; Wang, Q.; Zheng, W.; Shi, Q.; Liu, Y. (Nanoscale Res. Lett., 2015)

(untitled) - Kandulna, R.; Choudhary, R. B.; Maji, P. (J. Inorg. Organomet. Polym. Mater., 2017)

(untitled) - Özdemir, O.; Mucur, S. P.; Tekin, E.; Boudiba, S.; Ulbricht, C.; Egbe, D. A. M.; Deneb Menda, U.; Kavak, P. A.; Kutlu, K. (Proc. SPIE, 2013)

2006 IEEE International Conference on Semiconductor Electronics - Juhari, N.; Majid, W. H. A.; Ibrahim, Z. A. (Kuala Lumpur, Malaysia, 29.10.2006-1.12.2006)

(untitled) - Zhao, X.; Zhan, X. (Chem. Soc. Rev., 2011)

(untitled) - Burroughes, J. H.; Bradley, D. D. C.; Brown, A. R.; Marks, R. N.; Mackay, K.; Friend, R. H.; Burns, P. L.; Holmes, A. B. (Nature, 1990)

(untitled) - Han, D.-P.; Ishimoto, S.; Mano, R.; Lu, W.; Iwaya, M.; Takeuchi, T.; Kamiyama, S.; Akasaki, I. (Phys. Status Solidi A, 2020)

(untitled) - Lee, M.-L.; Wang, S.-S.; Yeh, Y.-H.; Liao, P.-H.; Sheu, J.-K. (Sci. Rep., 2019)

(untitled) - Ozen, Y.; Sertel, T.; Cetin, S. S.; Ozcelik, S. (J. Electron. Mater., 2018)

(untitled) - Salcedo-Reyes, J. C.; Vázquez, J.; Jiménez, L. C.; Méndez-Pinzón, H. (Proc. SPIE, 2017)

(untitled) - Coe-Sullivan, S.; Steckel, J. S.; Woo, W.-K.; Bawendi, M. G.; Bulović, V. (Adv. Funct. Mater., 2005)

(untitled) - Zhao, J.; Zhang, J.; Jiang, C.; Bohnenberger, J.; Basché, T.; Mews, A. (J. Appl. Phys., 2004)

(untitled) - Xu, J.; Wang, L.; Zhao, X.; Shi, Y.; Shi, Y.; Liu, T. (Nanomaterials, 2021)

(untitled) - Su, Q.; Zhang, H.; Chen, S. (npj Flexible Electron., 2021)

(untitled) - Shin, J. S.; Kim, T. Y.; Heo, S. B.; Hong, J.-A.; Park, Y.; Kang, S. J. (RSC Adv., 2021)

(untitled) - Bakueva, L.; Musikhin, S.; Hines, M. A.; Chang, T.-W. F.; Tzolov, M.; Scholes, G. D.; Sargent, E. H. (Appl. Phys. Lett., 2003)

(untitled) - Chaudhary, S.; Ozkan, M.; Chan, W. C. W. (Appl. Phys. Lett., 2004)

(untitled) - Choi, M. K.; Yang, J.; Hyeon, T.; Kim, D.-H. (npj Flexible Electron., 2018)

(untitled) - Lee, J. U.; Gipp, P. P.; Heller, C. M. (Appl. Phys. Lett., 2004)

(untitled) - Paulo-Mirasol, S.; Martínez-Ferrero, E.; Palomares, E. (Nanoscale, 2019)

(untitled) - Wang, F.; Chen, Y.-h.; Liu, C.-y.; Ma, D.-g. (Chem. Commun., 2011)

(untitled) - Guo, X.; Wang, C.-F.; Yu, Z.-Y.; Chen, L.; Chen, S. (Chem. Commun., 2012)

(untitled) - Li, X.; Liu, Y.; Song, X.; Wang, H.; Gu, H.; Zeng, H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Cui, B.; Feng, X.-t.; Zhang, F.; Wang, Y.-l.; Liu, X.-g.; Yang, Y.-z.; Jia, H.-s. (New Carbon Mater., 2017)

(untitled) - Ghosh, D.; Sarkar, K.; Devi, P.; Kim, K.-H.; Kumar, P. (Renewable Sustainable Energy Rev., 2021)

(untitled) - Masha, S.; Oluwafemi, O. S. (Mater. Lett., 2021)

(untitled) - Okamoto, K.; Niki, I.; Shvartser, A.; Narukawa, Y.; Mukai, T.; Scherer, A. (Nat. Mater., 2004)

(untitled) - Kwon, M.-K.; Kim, J.-Y.; Kim, B.-H.; Park, I.-K.; Cho, C.-Y.; Byeon, C. C.; Park, S.-J. (Adv. Mater. (Weinheim, Ger.), 2008)

(untitled) - Chen, S.-H.; Huang, C.-L.; Yu, C.-F.; Wu, G.-F.; Kuan, Y.-C.; Cheng, B.-H.; Li, Y.-R. (Opt. Lett., 2017)

(untitled) - You, J. B.; Zhang, X. W.; Dong, J. J.; Song, X. M.; Yin, Z. G.; Chen, N. F.; Yan, H. (Nanoscale Res. Lett., 2009)

(untitled) - Deng, L.; Yang, J.; Zhan, N.; Yu, T.; Yu, H.; Chen, S. (Opt. Lett., 2019)

(untitled) - Munkhbat, B.; Pöhl, H.; Denk, P.; Klar, T. A.; Scharber, M. C.; Hrelescu, C. (Adv. Opt. Mater., 2016)

(untitled) - Yu, T.; Deng, L.; Xia, P.; Lu, Y.; Zhan, N.; Chen, S. (Org. Electron., 2019)

(untitled) - Veinot, J. G. C.; Marks, T. J. (Acc. Chem. Res., 2005)

(untitled) - Yang, K. Y.; Choi, K. C.; Ahn, C. W. (Appl. Phys. Lett., 2009)

(untitled) - Klain, C.; Linde, S.; Shikler, R.; Sarusi, G. (Carbon, 2020)

(untitled) - Chang, J.-H.; Lin, W.-H.; Wang, P.-C.; Taur, J.-I.; Ku, T.-A.; Chen, W.-T.; Yan, S.-J.; Wu, C.-I. (Sci. Rep., 2015)

(untitled) - Chien, Y.-M.; Shih, I.; Izquierdo, R. (ECS Trans., 2019)